(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Da’wah institutions in the contemporary era face significant challenges in expanding their outreach amidst digital disruption. Rumah Tahfidz Baitul Arqom, an institution focused on cultivating a Qur’anic generation, has experienced significant constraints due to limited public visibility. This limitation is rooted in the absence of an adequate digital platform to support its da’wah mission. In response to this challenge, a community service activity was initiated with the primary goal of building a comprehensive and integrated digital ecosystem. This study reports a community service initiative aimed at enhancing the digital visibility of Rumah Tahfidz Baitul Arqom through the development of a sustainable digital ecosystem. The program applied a structured approach consisting of needs analysis, digital infrastructure development, and capacity building through training. The outputs include an official website integrated with a blog and the optimization of social media platforms. The results indicate improved institutional visibility, enhanced information accessibility, and increased managerial capacity in digital content management. This integrated approach ensures sustainability by combining user-friendly technology with capacity development. The study demonstrates that a holistic digital ecosystem can effectively support the transformation of traditional da’wah into a modern digital format.